Upward Magma Migration Within the Multi-Level Plumbing System of the Changbaishan Volcano (China/North Korea) Revealed by the Modeling of 2018–2020 SAR Data - Trasatti, Elisa; Tolomei, Cristiano; Wei, Lianhuan; Ventura, Guido (Frontiers in Earth Science, 2021)
Changbaishan volcano (China/North Korea border) was responsible for the largest eruption of the first Millennium in 946 CE and is characterized by a multi-level plumbing system. It last erupted in 1903 and presently consists of a cone with summit caldera. An unrest episode occurred between 2002 and 2006, followed by subsidence. Here, we analyze the Changbaishan 2018–2020 deformations by using remote sensing data, detecting an up to 20 mm/yr, NW-SE elongated, Line of Sight movement of its southeastern flank and a −20 mm/yr Line of Sight movement of the southwestern flank. This reveals an unrest occurring during 2018–2020. Modeling results suggest that three active sources are responsible for the observed ground velocities: a deep tabular deflating source, a shallower inflating NW-SE elongated spheroid source, and a NW-SE striking dip-slip fault. The depth and geometry of the inferred sources are consistent with independent petrological and geophysical data. Our results reveal an upward magma migration from 14 to 7.7 km. The modeling of the leveling data of the 2002–2005 uplift and 2009–2011 subsidence depicts sources consistent with the 2018–2020 active system retrieved. The past uplift is interpreted as related to pressurization of the upper portion of the spheroid magma chamber, whereas the subsidence is consistent with the crystallization of its floor, this latter reactivated in 2018–2020. Therefore, Changbaishan is affected by an active magma recharge reactivating a NW-SE trending fault system. Satellite data analysis is a key tool to unravel the magma dynamics at poorly monitored and cross-border volcanoes.